2000
DOI: 10.1097/00000478-200005000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin Section Immunophenotype of Cutaneous and Extracutaneous Mast Cell Disease

Abstract: Mast cell disease (MCD) is a rare proliferation that may be easily confused with other hematopoietic tumors. Several paraffin section antibodies immunoreact with mast cells but most are not specific. Tryptase, a specific marker of mast cells, may not be cost-effective to maintain in a laboratory because of the rarity of these lesions. This study was undertaken to assess the immunoreactivity of MCD and attempt to select a limited antibody panel for diagnosing MCD among hematopoietic tumors that morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…In addition, multiple recent and past studies have described the BMMC immunophenotype in detail [11][12][13][14][15][16] . In contrast, little is known about the immunophenotypic profile of skin MCs (sMCs) in patients with mastocytosis [17][18][19][20] . It has been reported that sMCs in mastocytosis patients may coexpress CD25 and CD4 but do not express CD2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, multiple recent and past studies have described the BMMC immunophenotype in detail [11][12][13][14][15][16] . In contrast, little is known about the immunophenotypic profile of skin MCs (sMCs) in patients with mastocytosis [17][18][19][20] . It has been reported that sMCs in mastocytosis patients may coexpress CD25 and CD4 but do not express CD2.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that sMCs in mastocytosis patients may coexpress CD25 and CD4 but do not express CD2. However, it has to be stressed that those studies were based on small groups of patients [17,19,20] . Furthermore, the frequency of CD2 and CD25 expression on sMCs has never been assessed in CM and SM patients, who were diagnosed strictly according to the WHO criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-triptase is the most sensitive and specific marker for the detection of normal and neoplastic mast cells, although anti-triptase reactivity was recently documented in a small cleaved cell lymphoma. 16 It should be noted that mast cells are nearly always positive for CD43, CD68, and CD117 and may show strong reactivity for chloracetate esterase, peroxidase, LCA, and CD11 C . 16 Finally, non-neoplastic lesions, such as osteomyelitis and eosinophilic granuloma, should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…16 It should be noted that mast cells are nearly always positive for CD43, CD68, and CD117 and may show strong reactivity for chloracetate esterase, peroxidase, LCA, and CD11 C . 16 Finally, non-neoplastic lesions, such as osteomyelitis and eosinophilic granuloma, should be considered in the differential diagnosis. The presence of plasma cells, polymorphonuclear leukocytes (PMNs), small mature lymphocytes, and capillary proliferation favors the diagnosis of osteomyelitis.…”
Section: Discussionmentioning
confidence: 97%
“…Yang et al assessed the immunophenotype of cutaneous and extracutaneous mast cell disease on paraffin sections and included in their study, four cases of MM without finding KIT expression [17]. Natkunam et al analyzed the utility of paraffin section immunohistochemistry for KIT in the differential diagnosis of systemic mast cell disease involving the bone marrow and found no expression of KIT in various B-cell lymphomas or plasma cell tumors [8].…”
Section: Discussionmentioning
confidence: 99%